2018
DOI: 10.3389/fnagi.2018.00354
|View full text |Cite
|
Sign up to set email alerts
|

Pre-aging of the Olfactory Bulb in Major Depression With High Comorbidity of Mental Disorders

Abstract: Recent studies suggest that accelerated aging of the brain is a neuroanatomical signature of the state of mental diseases. In major depression, this pre-aging effect is negatively associated with the duration since the first onset of the disease. The olfactory bulb (OB) shrinks with age in healthy subjects and patients with mental diseases show reduced OB volumes, especially those with major depression. It is unclear whether this OB reduction in mental diseases resembles a pre-aging process and whether it is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…In the DG, a steady stream of new neurons was maintained that can be projected into the cerebral cortex to regulate emotional and cognitive functions, which is closely related to depression symptoms and anxiety (F. L. Chao et al, 2018; J. Zhang et al, 2017). The olfactory bulb is crucial for behavioral changes in rodents, and its absence can lead to anxiety, depression, and mania (Rottstaedt, Weidner, Hummel, & Croy, 2018). The cerebellum is responsible for motor coordination, normal cerebellar function guarantees reliable behavioral results (Peterburs et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the DG, a steady stream of new neurons was maintained that can be projected into the cerebral cortex to regulate emotional and cognitive functions, which is closely related to depression symptoms and anxiety (F. L. Chao et al, 2018; J. Zhang et al, 2017). The olfactory bulb is crucial for behavioral changes in rodents, and its absence can lead to anxiety, depression, and mania (Rottstaedt, Weidner, Hummel, & Croy, 2018). The cerebellum is responsible for motor coordination, normal cerebellar function guarantees reliable behavioral results (Peterburs et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, volumetric changes of the OB, mainly by magnetic resonance imaging (MRI) assessment, have been reported in multiple brain disorders (Chen et al, 2014, 2018a; Li et al, 2016; Petekkaya et al, 2020). A reduction in the OB volume has also been reported in psychiatric disorders, such as major depressive disorders and SZ (Asal et al, 2018; Gul et al, 2015; Negoias et al, 2010; Nguyen et al, 2011; Rottstädt et al, 2018; Rottstaedt et al, 2018a, 2018b; Turetsky et al, 2000). Importantly, there are reports that indicate a volume reduction in subjects at high risk for psychosis (Turetsky et al, 2003, 2018), suggesting that the changes found in SZ and related disorders may not be due to secondary effects of medication.…”
Section: Introductionmentioning
confidence: 84%
“…Meanwhile, volumetric changes of the OB, mainly by magnetic resonance imaging (MRI) assessment, have been reported in multiple brain disorders [21][22][23][24] . A reduction in the OB volume has also been reported in psychiatric disorders, such as major depressive disorder and schizophrenia (SZ) [25][26][27][28][29][30][31][32] . Importantly, there are reports that indicate a volume reduction in subjects at high risk for psychosis 33,34 , suggesting that the changes found in SZ and related disorders may not be due to secondary effects of medication.…”
Section: Introductionmentioning
confidence: 97%